(untitled) (Scientific journal of the Fergana State University, 2025)
This research is conducted on the topic of "The Professional Theory and Practical Training of Educators," with the aim of studying the professional knowledge and skills of educators in the process of teaching preschool-aged children. The knowledge related to "Ontogeny," that is, the role of educators in the developmental process of children and their level of professional preparation, is of significant importance in enhancing the quality of education. The study examines the professional theory of educators, its application in practice, as well as the methods of monitoring the educational process in preschool educational institutions. The results of this research will serve to develop recommendations necessary for improving the professional qualifications of educators and organizing the educational process more effectively.